A multicomponent reaction of 2-aminoimidazoles: microwave-assisted synthesis of novel 5-aza-7-deaza-adenines12. Issue 81 (2nd November 2017) - Lim, Felicia Phei Lin; Low, Szy Teng; Ho, Elvina Lee King; Halcovitch, Nathan R.; Tiekink, Edward R. T.; Dolzhenko, Anton V.
Abstract : An efficient and highly selective multicomponent synthesis of 4-aminoimidazo[1, 2- a ]triazines, which are 5-aza-7-deaza-isosteres of adenine, was developed. Abstract : An efficient and highly selective multicomponent synthesis of 4-aminoimidazo[1, 2- a ][1, 3, 5]triazines, which are 5-aza-7-deaza-isosteres of adenine, was developed. The reaction of 2-aminoimidazoles, triethyl orthoformate and cyanamide under microwave irradiation proceeded regioselectively to provide a library of novel 5-aza-7-deaza-adenines in good yields and purity. The developed method was demonstrated to be scalable and highly reproducible in three different monomode microwave reactors. A rearrangement was proposed to explain the high selectivity of the reaction.